Functional Connectivity Density Mapping of Depressive Symptoms and Loneliness in Non-Demented Elderly Male - Lan, Chen-Chia; Tsai, Shih-Jen; Huang, Chu-Chung; Wang, Ying-Hsiu; Chen, Tong-Ru; Yeh, Heng-Liang; Liu, Mu-En; Lin, Ching-Po; Yang, Albert C. (Frontiers in Aging Neuroscience, 2016)
Background: Depression and loneliness are prevalent and highly correlated phenomena among the elderly and influence both physical and mental health. Brain functional connectivity changes associated with depressive symptoms and loneliness are not fully understood. Methods: A cross-sectional functional MRI study was conducted among 85 non-demented male elders. Geriatric depression scale-short form and loneliness scale were used to evaluate the severity of depressive symptoms and loneliness, respectively. Whole brain voxel-wise resting-state functional connectivity density (FCD) mapping was performed to delineate short-range FCD (SFCD) and long-range FCD (LFCD). Regional correlations between depressive symptoms or loneliness and SFCD or LFCD were examined using general linear model, with age incorporated as a covariate and depressive symptoms and loneliness as predictors. Results: Positive correlations between depressive symptoms and LFCD were observed in left rectal gyrus, left superior frontal gyrus, right supraorbital gyrus, and left inferior temporal gyrus. Positive correlations between depressive symptoms and SFCD were observed in left middle frontal gyrus, left superior frontal gyrus, bilateral superior medial frontal gyrus, left inferior temporal gyrus, and left middle occipital region. Positive correlations between SFCD and loneliness were centered over bilateral lingual gyrus. Conclusion: Depressive symptoms are associated with FCD changes over frontal and temporal regions, which may involve the cognitive control, affective regulation, and default mode networks. Loneliness is associated with FCD changes in bilateral lingual gyri that are known to be important in social cognition. Depressive symptoms and loneliness may be associated with different brain regions in non-demented elderly male.